TECHNOLOGY BASED EDUCATION: USING PADLET FOR AN EFFECTIVE CLASSROOM ENVIRONMENT - Jayamini Ratnayake; Stephanie Perera (PUPIL: International Journal of Teaching, Education and Learning, 2025)
Technology has revolutionized the modern classroom with innovative tools that have replaced traditional methods of teaching and learning for both educators and students. This research study explores the effectiveness of using Padlet, an online platform which allows students to share their thoughts, ideas, opinions and information on enhancing their learning while boosting their creativity, collaboration, critical thinking, and communication skills. For the purpose of this study, a workshop on the use of Padlet was conducted for lecturers and students at the American College of Higher Education in Sri Lanka. The students varied from certificate-level, diploma-level, and foundation courses, and the lecturers were those who taught these courses. The workshop was held to train both lecturers and students to incorporate Padlet in their teaching - learning process. To evaluate its impact on the participants, questionnaires were distributed to 100 students of the above courses and 20 lecturers. The questionnaires for both students and lecturers consisted of three parts; demographic information, closed-ended questions rated on a 5-point Likert scale, and open-ended questions where both students and lecturers had to write their opinions and views on the effective use of the Padlet tool. IBM SPSS Statistics 27.0.1 software was used to analyse the data collected from the participants and it was concluded that using the Padlet tool was effective and efficient to boost creativity, collaboration, critical thinking, and communication skills. The study also revealed that the padlet tool reduces negative affective filters such as anxiety, lack of motivation, and low self-esteem, thereby fostering more effective learning. The study reinforces the positive role of digital technology like Padlet in fostering and enhancing student engagement for an effective classroom environment.